MEDICAL COLLEGES ADMISSION TEST IN PUNJAB, PAKISTAN - Khan, Junaid Sarfraz; Biggs, John SG; Bano, Tahira; Mukhtar, Osama; Tabasum, Saima; Mubasshar, Malik Hussain (Journal of Ayub Medical College Abbottabad, 2013)
Background: Nearly 18,000 candidates securing 60% and above marks in Higher Secondary School Certificate (HSSC) examination contest for admission in Medical Colleges, in Punjab, Pakistan by sitting in the Medical College Admission Test (MCAT) each summer. This cross-sectional study was conducted to identify patterns related to demographic, economic and educational backgrounds, over a two-year-period, in this population, and how HSSC and MCAT marks predict future performance of the selected candidates. Methods: Marks obtained by candidates in HSSC, MCAT, and 1st Professional MBBS (Part-I) Examinations over two years 2008-2009, were analysed using parametric tests in SPSS. Results: Total 18,090 candidates in 2008 and 18,486 in 2009 sat in the MCAT. National HSSC candidates scored higher marks in HSSC and MCAT but lower marks than their foreign qualified HSSC counterparts (e.g., Advanced-Levels from Cambridge University, UK) in Part-I overall and in all its sub-components individually (p<0.05). Female students scored higher marks than males in HSSC (p>0.05), MCAT (p>0.05) and Part-I theory, practical, viva voce, continuous assessment and Objective-Structured Performance Evaluation (OSPE) components (p<0.05). In both years, students from the Dera Ghazi Khan District scored the highest marks in the HSSC Examinations (p<0.05) but least marks in MCAT in 2008 (p<0.05) and in Part-I in 2008 and 2009 (p<0.05). Students from '˜tougher' Boards like Rawalpindi in 2008 and the Federal Board in 2009 who scored least marks in HSSC scored highest marks in MCAT, and in Part-I Examinations (p<0.05). Linear regression on Part-I by taking HSSC and MCAT marks as independent variables showed that the MCAT marks exerted the greatest positive influence consistently at 0.104 (2008) and 0.106 (2009). In 2009 HSSC marks were shown to exert a negative influence (-0.08) on Part-I. Conclusion: There is need to standardise HSSC education and examination across all Intermediate Boards. MCAT is a better predictor of Medical Students' future performance. Keywords: Higher Secondary School Certificate, MCAT, demographic, socio-economic, assessment